Smoking Cessation Experience and Socioeconomic Status of Online Motorcycle Taxi Drivers in Surabaya - Amelia Lorensia; Rivan Virlando Suryadinata (Media Kesehatan Masyarakat Indonesia, 2021)
Online motorcycle taxi drivers are at risk of experiencing exposure to air pollution, and smoking habits can exacerbate the risk of decreased lung function. The success of smoking cessation could be influenced by the experience of cessation and socioeconomic status. In this regard, the study aimed to investigate the success of smoking cessation of online motorcycle taxi drivers in Surabaya, Indonesia, using a cross-sectional design from May–December 2020. A questionnaire was used to collect data through interviews, and the data were analyzed using a chi-square test. The number of respondents was 92. Among the respondents, 43.5% failed to quit smoking, while 56.5% of them succeeded. The chi-square test results demonstrated a relationship between all experience factors and the success of smoking cessation. Additionally, a relationship between education level (p<0.001) and income level (p<0.001) with socioeconomic status was observed. Further research is needed to observe how other factors such as knowledge, motivation, and environmental factors affect smoking cessation.